Blood Pressure and White Matter Lesions in Patients with Vascular Disease: The SMART-MR Study - Vlek, A. L.M.; Visseren, F. L.J.; Kappelle, L. J.; Witkamp, T. D.; Vincken, K. L.; Mali, W. P.; Graaf, Y. v. d. (Current Neurovascular Research, 2009)
White matter lesions (WML) are a frequent finding on brain magnetic resonance imaging scans. Elevated blood pressure (BP) is consistently identified as risk factor for WML. However, it is unknown whether BP still is associated with WML in patients manifesting vascular disease. The aim of this cross-sectional study was to investigate associations between BP and WML in patients manifesting vascular disease. A total of 1030 patients with vascular disease (cerebrovascular disease (23%), coronary heart disease (59%), peripheral arterial disease (23%), abdominal aortic aneurysm (9%)) from the Second Manifestations of Arterial Disease study were included. WML volume was calculated using an automated quantitative volumetric method and subsequently divided into quartiles. We investigated associations between BP and WML and examined whether relations between BP and WML were modified by the localisation of the symptomatic site or presence of diabetes. Participants had a mean age of 58.7 years. Median volume of WML was 1.70 ml. Mean BP was 141/82 mmHg and 69% suffered hypertension. No significant associations between systolic BP, diastolic BP, mean arterial pressure (MAP) or hypertension presence and moderate or large WML volumes were present. The relation between BP and WML was not modified by the localisation of vascular disease or diabetes presence. Among patients manifesting vascular disease, BP was not associated with the presence of WML, irrespective of the presence of diabetes or the localisation of vascular disease.
Keywords: vascular disease